Characterization, pathogenicity and anastomosis groups of Rhizoctonia solani from watermelon - Galvão, Kecia Mayara de Araújo; Cunha, Fábio Sanchez da; Ishikawa, Francine Hiromi; Costa, Antonio Elton da Silva; Capucho, Alexandre Sandri (Comunicata Scientiae, 2019)
The objective of this study was to characterize the morphological and pathogenic variation of Rhizoctonia solani isolates as well as to determine mycelial compatibility and hyphal fusion. The R. solani isolates CMM1053, CMM2967, CMM1052, CMM2983, CMM2971 and CMM3890 from watermelon were used. The determination of aggressiveness was evaluated using the six isolates inoculated in the Crimson Sweet susceptible cultivar in a completely randomized design (CRD) with five replicates, the sample unit consisting of one plant. The experiment of mycelial growth rate was installed in the factorial scheme, 6 isolates x 3 culture media, using the following culture media Nutrient Agar, PDA and PSA, and a total of 5 replicates. The color characterization and sclerotia formation was performed 15 days after the fungal inoculation in each culture medium. For the characterization of vegetative compatibility and occurrence of hyphal fusion, the experiments were performed in CDR with three and two replicates, respectively. CMM1053 and CMM1052 isolates were the most aggressive; however, they were statistically different only from CMM2967 isolate. The PSA medium was the most promising for the mycelial growth. It was possible to observe that there was variability in the colonies color, being higher in the Nutrient Agar medium. Based on evaluations of vegetative compatibility and hyphal fusion, the six isolates belong to the same anastomosis group.